A positive theory of income taxation - Oriol Carbonell-Nicolau (Rutgers University, Department of Economics, 2007)
We propose a dynamic version of the standard two-party electoral competition model adapted to nonlinear income taxation. The theory has a number of desirable features. First, equilibria always exist, even though the set of admissible tax policies is multidimensional. Second, the Nash set can be characterized generically, and its components give sharp predictions. Third, the features of equilibrium tax policies depend only on empirically meaningful fundamentals. Equilibrium tax schedules benefit the more numerous income groups and place the burden of taxation on income groups with fewer voters. For empirical income distributions, the features of an equilibrium tax schedule are reminiscent of Director's law of public income redistribution (Stigler [36]).
Keywords: H23; H31; D72; D78; 330; Nonlinear income taxation; electoral competitionh; Director's law; extensive zero-sum game; Einkommensteuerpolitik; Steuertheorie; Einkommensumverteilung; Wahlkampf; Public Choice; Dynamisches Modell; Theorie